PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAAN KERJA KARYAWAN PONDOK PESANTREN AL-QUR’AN HARSALLAKUM BENGKULU - Arisandi, Jefri; B, Idwal; Shar, Aan (ITB AAS Indonesia Surakarta, 2024)
This exploration intends to see if the factors of remuneration and inspiration impact worker work fulfillment. The object of this exploration is the Harsallakum Bengkulu Al-Qur'an Islamic Live-in School. In this examination, a quantitative methodology was utilized. The populace in this review was all representatives from the Harsallakum Bengkulu Al-Qur'an Islamic Life experience School, adding up to 60 individuals. The inspecting strategy utilizes the enumeration/complete testing technique, which is an examining procedure where all individuals from the populace are tested. So the quantity of tests utilized was 60 respondents. In this examination, numerous direct relapse examination is utilized as an information investigation technique. In view of the tests that have been done, it tends to be seen that the factors remuneration (X1) and inspiration (X2) to some extent impact representative work fulfillment. Then, all the while or together, the factors of pay and inspiration essentially affect worker work fulfillment at the Harsallakum Al-Qur'an Islamic live-in school, Bengkulu.